Application of Values Education in Islamic Religious Education - Nuryadi, Nuryadi (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to examine the implementation of value education within the context of Islamic education. The research utilizes a literature review method with a descriptive-analytical approach to collect and analyze data from various written sources, such as scholarly journals and books. The analysis is conducted qualitatively and conceptually to identify patterns and relationships relevant to the research topic. The application of value education in Islamic religious education aims to shape an ideal human being according to Islamic teachings by instilling deep moral and religious values. Islamic religious education must be based on the Qur'an and Hadith, integrating Islamic values into all aspects of education to develop insan kamil (a complete human being). Evaluation in Islamic religious education should also be comprehensive, addressing students' intellectual, moral, and skill development to ensure their growth aligns with the universal values of Islam.